Influence of PODE1 additive into ethanol-gasoline blends (E10) on fuel properties and phase stability - Awad, Omar I.; Zhou, Bo; Chen, Zhenbin; Kadirgama, Kumaran; Mohammed, M. N.; Devarajan, Ramasamy (Elsevier Ltd, 2023)
Polyoxymethylene dimethyl ethers (PODEn, n = 1–8) as an oxygenated fuel are a promising alternative fuel with a high oxygen concentration, a low C:H ratio, and no C–C bonds in their chemical structure. This could lead to smoke-free combustion. In this study, we chose to focus on PODE1 because of its lower cetane number, which makes it more suitable for use in spark ignition (SI) engines. However, its lower boiling point and octane number remain challenges. A low boiling point may lead to high vapour pressure and require storage and handling comparable to gaseous fuels. We investigated the effect of adding PODE1 to gasoline-ethanol blends (E10) on fuel properties, including distillation curve, octane number, phase stability, C/O/H ratio, heat of combustion, kinematic viscosity, and density. Our results showed that the blended fuels of E10 and PODE1 are stable up to 10 % PODE1, and there was no phase separation. Additionally, up to 10 % PODE1 additive had no significant side effect on the fuel properties of E10, particularly boiling point and octane number. Thus, work offers creative points by proposing a new candidate for additive fuel to gasoline-ethanol blends, which contributes to reducing the soot emission of GDI engines.